Geography at Vocational Schools in Baden-Württemberg Between Requirement and Reality: A Current Survey of Internal and External Opinions - Rausch, Bernhard; Siegmund, Alexander; Schmeinck, Daniela (Journal of Geography Education, 2005)
Again and again the school subject geography stands in the centre of the discussion concerning hour reductions in the education plans. The vocational school thereby frequently plays a decisive role to lead the way. Therefore the current situation of the subject economic geography at vocational schools in Baden-Württemberg is demonstrated exemplary in this article. Referring to this a questioning of pupils, parents and teachers from commercial schools about their opinions about the impact of the subject and the importance of geographical questions in and except the school context stands in the centre. In the range of the analysis it becomes clear, that the reputation of geography in the public opinion is substantially better than expected (feared). Especially the importance of the subject for the environmental education, the ability to orientate and to behave in the area is often mentioned by the respondents. Thus a central function is attached to geography. A central position that is essential to strengthen it in the public discussion.